Augmented-reality swim goggles accurately and reliably measure swim performance metrics in recreational swimmers - Eisenhardt, Dan; Kits, Aidan; Madeleine, Pascal; Samani, Afshin; Clarke, David C.; Kristiansen, Mathias (Frontiers in Sports and Active Living, 2023)
Background: The purpose of this study was to assess the validity and reliability of the FORM Smart Swim Goggles compared to video analysis for stroke type, length count, length time, stroke rate and stroke count in recreational swimmers and triathletes. Method: Thirty-six participants performed mixed swimming intervals in a 25-meter pool across two identical 900-meter swim sessions performed at comparable intensities one week apart. Participants wore FORM Goggles during their swims, which detected the following five swim metrics: stroke type, length time, length count, stroke count and stroke rate. Four video cameras were positioned on the pool edges to capture ground-truth video footage, which was then manually labeled by three trained individuals. Mean (SD) differences between FORM Goggles and ground truth were calculated for the selected metrics for both sessions. Absolute Mean Difference and Mean Absolute Percentage Error were used to assess the differences of the FORM Goggles relative to ground truth. Test-retest reliability of the goggles were assessed using both relative and absolute reliability metrics. Results: Compared to video analysis, the FORM Goggles identified the correct stroke type at a rate of 99.7% (N = 2354 lengths, p < 0.001), length count accuracy of 99.8%, and mean differences (FORM Goggles – ground-truth) for length time: -0.10s (1.49); stroke count: -0.63 (1.82), and stroke rate: 0.19 strokes/min (3.23). The test-retest ICC values between the two test days were 0.793 for length time, 0.797 for stroke count, and 0.883 for stroke rate. Overall, for length time the residuals were within ±1.0s for 65.3% of total lengths, for stroke count within ±1 stroke for 62.6% of total lengths, and for stroke rate within ±2 strokes/min for 66.40% of total lengths. Conclusion: The FORM Goggles were found valid and reliable for tracking of length time, length count, stroke count, stroke rate, and stroke type during freestyle, backstroke, and breaststroke swimming in recreational swimmers and triathletes when compared to video analysis. This opens perspectives for receiving real-time information on performance metrics during swimming.